Craniopharyngiomas in the posterior fossa: a rare subgroup, diagnosis, management and outcomes. Issue 10 (17th September 2009) - Zhou, L; Luo, L; Xu, J; Li, Q; Chen, J; Jiang, S; Cai, B; You, C
Abstract : Objective: Craniopharyngiomas with predominant pars in the posterior fossa are very rare and extremely overlooked. The clinical features, diagnosis and management are different from their sellar/suprasellar counterparts. The purpose of this study was to explore the differing characteristics of posterior fossa craniopharyngiomas. Methods: Seven patients with pathologically proven craniopharyngiomas located in the posterior fossa were retrospectively investigated. The clinical data and radiographic findings were presented and analysed. Results: The primary presentations included headache, diplopia, ataxia and hearing loss. All tumours were located in the retrochiasmatic area, and five of seven displayed a retroinfundibulum growth pattern. The predominant components of the tumours were located in the unilateral cerebellopontine angle (CPA) in six cases, and the bilateral CPA in one case. Total tumour resection was accomplished in five patients. There were transient cranial nerve deficits in three patients, and CSF leakage in one patient. Six patients fully recovered to normal conditions, but one patient had tumour regrowth and had to undergo a secondary resection. Conclusions: Posterior fossa craniopharyngiomas are rare and may be considered an independent subgroup of classifications. Tumours arising from the sellar region and extending to the posterior fossa present with their own unusual set of characteristics. These tumours can be radically and safely removed with a combined supra- and intratentorial approach.